2010
DOI: 10.1159/000297508
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effects of Prednisolone and Olopatadine on Atopic Dermatitis Model of Hairless Mice

Abstract: We investigated the synergetic effects of glucocorticoid and histamine H1 receptor antagonists on an atopic dermatitis model. Hairless mice were used in this study and an atopic dermatitis model was made by repeated application of 2,4,6-trinitrochlorobenzene. The effects of glucocorticoid, histamine H1 receptor antagonists, and the simultaneous use of these drugs were investigated by measuring scratching behavior, skin symptoms and nerve growth factor (NGF) in the skin. Topical application of prednisolone sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In support of this hypothesis, the antihistamine olopatadine was shown in vivo to enhance prednisolone inhibition of scratching and skin symptoms in an atopic dermatitis murine model (Kagawa et al, 2010). Likewise, H 1 R blocker azelastine reduced the frequency of administration of inhaled corticosteroids without loss of pulmonary function in a clinical trial with patients with chronic asthma (Busse et al, 1996).…”
Section: Histaminergic Regulation Of the Signaling Of Other Receptorsmentioning
confidence: 90%
“…In support of this hypothesis, the antihistamine olopatadine was shown in vivo to enhance prednisolone inhibition of scratching and skin symptoms in an atopic dermatitis murine model (Kagawa et al, 2010). Likewise, H 1 R blocker azelastine reduced the frequency of administration of inhaled corticosteroids without loss of pulmonary function in a clinical trial with patients with chronic asthma (Busse et al, 1996).…”
Section: Histaminergic Regulation Of the Signaling Of Other Receptorsmentioning
confidence: 90%
“…A study from 2011 showed that the combination of both drugs is the most widely-used option in routine clinical practice to treat all types of AR 2 , and three patents have been recently granted to formulations containing the antihistamine azelastine with the synthetic corticosteroids mometasone furoate, ciclesonide and fluticasone propionate 3 . Likewise, concerning AD, the synergistic effects of glucocorticoids and antihistamines have been evaluated in an animal model, where olopatadine potentiated the inhibitory effect of prednisolone on the relief of the inflammatory symptoms leading to the conclusion that this drug combination is useful to treat AD, although the mechanism underlying the synergism was not investigated 41 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of NO in AD, as well as the role of NO in rhinitis, remains to be elucidated. Recent studies demonstrate the development of a mouse model whose symptoms are similar to those in patients with AD (10–12). These mice show increased scratching and marked elevation of immunoglobulin E (IgE) in plasma, particularly when challenged with allergens.…”
Section: Introductionmentioning
confidence: 99%